Escola complementar e normal de Piracicaba: formação, poder e civilidade (1897-1921) - Honorato, Tony [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
This thesis is a research about the history of Complementary and Normal School of Piracicaba, figures modeled in training primary school teachers within the State of São Paulo. Searched as was the historical process of Complementary and Normal School of Piracicaba (1897-1921). It was aimed to interpret the constitution of the Schools of Piracicaba as figurations, to characterize teacher training as a reference and demonstrate civilizing power relations based on the elements of school culture. The theoretical and methodological procedures fell on the proposal of Norbert Elias, particularly Figurational Sociology and Theory of Civilizing Processes. It was elected, as a primary source historical manuscripts, printed papers and legislation. The period defined between 1897 and 1921 justifies its inception in 1897 by the introduction of Complementary Piracicaba and its end because its transformation into Normal School, which was considered as a reference in the context of the Reformation of 1920, given its educational and cultural effervescence caused by a group of teachers and intellectuals linked to Sampaio Dória. It was concluded that, in addition to producing the image of modern man and civilized society in Republican figurations Piracicaba lived along its historical balance of power in a network of schools to train teachers, thus implying a further reduction of power the prestigious Escola Normal da Capital

Esta tese constitui uma pesquisa acerca da história da Escola Complementar e Normal de Piracicaba, figurações modelares na formação de professores primários no interior do Estado de São Paulo. Pesquisou como ocorreu o processo histórico da Escola Complementar e Normal de Piracicaba (1897-1921). Objetivou interpretar a constituição das Escolas de Piracicaba como figurações, caracterizar a formação de professores como referencial civilizador e demonstrar relações de poder fundadas nos elementos da cultura escolar. Os procedimentos teórico-metodológicos recaíram sobre a proposta de Norbert Elias, em particular a Sociologia Figuracional e a Teoria dos Processos Civilizadores. Elegeu como fonte primária histórica manuscritos, impressos e legislações. O período delimitado entre 1897 e 1921, justifica seu início pela instauração em 1897 da Complementar de Piracicaba e seu término em razão da sua transformação em Escola Normal, que foi considerada como referência no contexto da Reforma de 1920, dada sua efervescência pedagógica e cultural provocada por um grupo de professores e intelectuais ligados à Sampaio Dória. Concluiu-se que, além da produção da imagem do homem moderno e civilizado na sociedade republicana, as figurações piracicabanas viveram ao longo do seu processo histórico um equilíbrio de poder na rede de escolas para formar professores, por conseguinte implicando ainda mais a redução de poder da prestigiosa Escola Normal da Capital
Keywords: Educação; Escolas; Professores - Formação; Schools; Piracicaba (SP)